APLIKASI E-ARSIP PADA STMIK PALCOMTECH PALEMBANG - Atin Triwahyuni (Seminar Nasional Informatika (SEMNASIF), 2011)
Student administration archiving system of STMIK PalComTech Palembang, mostly still concentrated in the BAAK (Administrative Bureau of Academic Affairs). And without realizing it, will affect to the performance of administrative staff which finally can cause the service to the academic community to be slow.With the information technology, expected part of the burden of administration staff in providing information services contributed. So that activities that should be the duties and responsibilities of administrative staff can be carried out optimally.For this reason, student administration archiving system created digitally (e-archive), using OCR system (Optical Character Recognition) and string search methods (String Matching). For analysis and design, we use PHP as the programming language and MySQL as the database.This study aims to develop a digital archiving system (e-archive) with the help of the shelter database as the data, thus making the performance of administrative staff, especially BAAK getting better and professional in service quality